1989
DOI: 10.1016/0377-8398(89)90031-5
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene-Pleistocene radiolarian events and magnetostratigraphic calibrations for the tropical Indian Ocean

Abstract: Johnson, D.A., Schneider, D.A., Nigrini, C.A., Canlet, J.P. and Kent, D.V., 1989. Pliocene-Pleistocene radiolarien events and magnetostratigraphic calibrations for the tropical Indian Ocean. Micropaleontol., 14: 33-64.A composite of four piston cores from the Central Indian Basin and adjacent Ninetyeast Ridge has yielded a continuous magnetobiostratigraphic reference section for most of the Pliocene and the Pleistocene (0.0-4.5 Ma). We identified thirty-three radiolarian events (first-or last-occurrences), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 45 publications
10
88
1
Order By: Relevance
“…These assignments were checked using the nannofossil datums, the LAD of Reticulofenestra pseudoumbilica (NN16/ NN15) and the LAD of Phormostichoartus doliolum, (NN12/ NN11) (Spaulding, this volume). They are also concordant with the published ages of the radiolarian events, the LAD of Phormostichoartus doliolum, FAD of Amphirhopalum ypsilon, FAD of Spongaster tetras, and LAD of Solenosphaera omnitubus (Nigrini, this volume; Johnson and Nigrini, 1985;Johnson et al, 1989). The magnetostratigraphic results suggest that the sedimentation rate was higher in the Pliocene, especially during the late and middle Gilbert Chron (C2Ar and C3).…”
Section: Site 728supporting
confidence: 88%
See 1 more Smart Citation
“…These assignments were checked using the nannofossil datums, the LAD of Reticulofenestra pseudoumbilica (NN16/ NN15) and the LAD of Phormostichoartus doliolum, (NN12/ NN11) (Spaulding, this volume). They are also concordant with the published ages of the radiolarian events, the LAD of Phormostichoartus doliolum, FAD of Amphirhopalum ypsilon, FAD of Spongaster tetras, and LAD of Solenosphaera omnitubus (Nigrini, this volume; Johnson and Nigrini, 1985;Johnson et al, 1989). The magnetostratigraphic results suggest that the sedimentation rate was higher in the Pliocene, especially during the late and middle Gilbert Chron (C2Ar and C3).…”
Section: Site 728supporting
confidence: 88%
“…As shown in Figure 4, these assignments are concordant with the horizons of the Pliocene radiolarian events (Nigrini, this volume), of which ages were paleomagnetically calibrated using DSDP and piston cores from the Equatorial Indian and Pacific Oceans (Johnson and Nigrini, 1985;Johnson et al, 1989). Polarity intervals of about or less than 10 5 yr were not clearly detected; as at Site 721, the Olduvai (C2), Kaena (C2A-1), and Mammoth (C2A-2) subchronozones were not observed in Hole 722A and 722B.…”
Section: Site 722supporting
confidence: 66%
“…The only two such events were the First Occurrence (FO) of Buccinosphaera invaginata, dated at 0.18 Ma [7], and the Last Occurrence (LO) of Stylatractus universus, dated at 0.42 Ma [8]. B. invaginata, a colonial, warm-water adapted species, is reported as very rare in modern sediments from the South Atlantic, reaching maximum abundances (however, up to only 1%), in the South Atlantic Central Gyre [9].…”
Section: Evidence Against Sources Of Error In the Sst Interpretationmentioning
confidence: 99%
“…These two genera were well represented in Leg 115 material, but a number of the taxa occurred only sporadically. Consequently, the following events that were identified previously (Johnson et al, 1989) A number of other significant late Neogene events were not possible to identify, including the following:…”
Section: Radiolarian Eventsmentioning
confidence: 99%
“…The FO of Amphirhopalum ypsilon, at 3.8 Ma in the upper part of the Gilbert (Johnson et al, 1989), is identified between 31.0 and 34.0 mbsf in Hole 710A (Appendix B). Thus, the long intervals of reversed polarity in Core 115-710A-4H (Backman et al, in press, fig.…”
Section: Paleomagnetic Calibrations and Diachroneitymentioning
confidence: 99%